Biosecurity in the dairy - Gerald L. Stokka; Thomas R. Falkner; Patrick Bierman (Kansas Agricultural Experiment Station Research Reports, 1997)
Three strategies exist to control unwanted disease in a livestock operation: 1) prevent the douintroduction of infected cattle, 2) raise the overall level of resistance and specific resistance to infectious disease, and 3) minimize herd exposure to infectious disease. In addition, if unwanted disease exists in the herd, then a plan to eliminate the disease should be implemented. Maintenance of closed herds, testing procedures, vaccination schedules, sanitation, and good husbandry practices are integral parts of biosecurity procedures. The procedures in place should produce a benefit in terms of both economics and public perception that the quality and safety of our food supply is of the utmost importance to livestock producers. Livestock units exist for the purpose of purproducing a nutritious food product, which is comaccomplished through the use of forages and cereal grains. This system benefits the producer enterby adding value to renewable resources. Society addibenefits through the availability of a wholesome, safe, food supply in addition to the creation of new wealth within our economic system. The time has come for the food production industry, especially the dairy and beef sectors, to recognize the benefits of biosecurity procedures. Those of us involved in the food production particubusiness must always keep in mind the importance of maintaining healthy animals and a healthy food supply.; Dairy Day, 1997, Kansas State University, Manhattan, KS, 1997;
Keywords: Dairy Day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-100-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 792; Biosecurity; Dairy; Disease; Management